Institutional Capacity for Science Diplomacy in Central America - Jarquin-Solis, Maria Esteli; Mauduit, Jean-Christophe (Frontiers in Research Metrics and Analytics, 2021)
Science, technology, and innovation (STI) is increasingly gaining in importance on the foreign policy agenda of governments worldwide. However, the implementation of science diplomacy strategies requires STI institutional capacity and strong interfaces with policy and diplomacy. This research first maps the STI public institutions of the six member countries of the Central American Integration System (Guatemala, El Salvador, Honduras, Nicaragua, Costa Rica and Panama) and then draws their capacity to connect internationally in order to highlight their potential for science diplomacy. Variables such as the year of creation and mandates of scientific councils, secretariats, national academies, international cooperation departments and ministries are analyzed. The study reveals several public management challenges stemming from the institutional disparity and complexity of the region, already marked by significant asymmetries of human development between the various countries. Highlighting and understanding such challenges may be helpful for countries in the region in developing meaningful strategies around science diplomacy.